Aksesibilitas di Grhatama Pustaka berdasarkan perspektif inklusi penyandang disabilitas (Sebuah kajian perpustakaan inklusif) - Yumna, Atikah Nur Aini; Masruri, Anis; Sholihah, Husna Amalina (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
The purpose of this research is to find out the strategy to create an inclusive library, including in the Grhatama Pustaka (Grhatama Library). The research method used is descriptive qualitative. Data collection was obtained through interviews with librarians, observation, and documentation. The results showed that the Grhatama Library to realize an inclusive library was carried out through 3 aspects, namely the function aspect as an information provider, the facility aspect whose design was friendly to disability, and the human resource aspect through training, but this had not been carried out thoroughly but the library took the initiative to hold a Braille Literacy event (LIBRA) and Whispering Cinema or Whispering Screen (LASIK). Keywords: library, inclusive, disability